Optimal treatment of chronic pain - Irving, Gordon (Henry Stewart Talks, 2009)
Dealing with the difficult and complex non-malignant pain patient, It is important to recognize both psychosocial and psychiatric co-morbidities, Having the patient become part of the solution and having them set realistic goals is important, Drugs used are similar to those used for cancer pain management but greater awareness of long term effects of opioids such as hyperalgesia and immune suppression, as well as diversion is important
Archived at 2021/02/25